Concentration camps on the home front : Japanese Americans in the house of Jim Crow - Howard, John, 1962- (University of Chicago Press, 2008)
Without trial and without due process, the United States government locked up nearly all of those citizens and longtime residents who were of Japanese descent during World War II. Ten concentration camps were set up across the country to confine over 120,000 inmates. Almost 20,000 of them were shipped to the only two camps in the segregated South--Jerome and Rohwer in Arkansas--locations that put them right in the heart of a much older, long-festering system of racist oppression. The first history of these Arkansas camps, Concentration Camps on the Home Front is an eye-opening account of the inm.